Prevalence of scabies and head lice among children in a welfare home in Pulau Pinang, Malaysia - Zayyid, M.M.; Saadah, R.S.; Adil, A.R.; Rohela, M.; Jamaiah, I. (2010)
This is a survey of 120 children for scabies and head lice infestations in a welfare home in Pulau Pinang. Children from this welfare home (Rumah Kanak-Kanak Taman Bakti, Kepala Batas, Pulau Pinang) were randomly selected. Majority of them were Malays (72.5) and the rest were Indians. The infestation rates were highest in the 10-12 years age group with 46 and 70 for scabies and head lice respectively. Head lice was more commonly seen in girls (65) than boys (29). Scabies was more commonly seen in boys (50) than girls (16). Overall prevalence rate for scabies was 31 and for head lice infestation was 49.